Guarding the guardians – examination of the EU rules limiting the power of market gatekeepers - Aivio, Anne (My University, 2023)
EU pursues its objectives though a barrier free single market, where free movement of goods, services, capital, and persons prevails, and environment guaranteeing fair and open competition among businesses is promoted. Any party – gatekeeper - capable of hindering access to markets needs to be guided by rules preventing this. The key rules guiding the gatekeepers consist of free movement articles and competition articles in the Treaty on the Functioning of the European Union (TFEU). The provisions of these articles are enhanced with a high number of lower-level rules and regulations, and principles developed by the European Court of Justice (ECJ) in its case law. The purpose of this work is to find the key rules and principles guiding the gatekeepers capable of hindering access to the EU markets, see who the relevant gatekeepers in the current market circumstances are, and to examine the coherence and coverage of the set of rules guiding these gatekeepers. The research method used is legal dogmatic. The coherence and coverage of the set of relevant rules is examined by first going through the key rules and relevant court cases providing further guidance per area (the key rules are collected on tables), and by then gradually constructing the big picture out of the reviewed details. The gatekeepers in the scope of the free movement rules and competition rules are identified. Also, new type of gatekeepers that have emerged along with new business models related to a platform economy, and rules to guide these (Digital Markets Act, DMA) are incorporated into the consideration. The systematic comparison of the rules and the logic that the Court has used when applying the rules reveals some points of vagueness. Also, the different logic for applying the rules in different areas, and possible overlaps of the legal areas raise questions. Whether a horizontal application can come to question regarding different free movement rules is relevant to finding a correct kind of logic for the application of the rules of different areas. Traditionally, the Member States have been the addressees of the free movement rules, and undertaking the addressees of the competition rules, but during the last few decades the court has applied the free movement laws also to Labour Unions, Sports Organizations, and even private companies. Now the question belongs: are there limitations to including private gatekeepers in the scope of the free movement laws, or can both types of rules be applied also to private parties? If yes, how is the logic for deciding which rules to prevail? The logic of applying the rules is different per area: for example, on the side of the competition laws the market power is evaluated when making decisions on the applicability, while on the side of free movement laws the qualities, like size, of the gatekeepers has had no relevance on application. To answer the above question, and to clarify the application of the rules in different practical cases, a simplified overall objective-driven model was introduced in the work. It is proposed that the horizontal application of the free movement rules is allowed on the effect utile basis when relevant – like the case seems to be now. However, in addition to for example the Digital Markets Act, also the competition rules are considered lex specialis and thus, given precedence over the free movement rules. The free movement rules are to be used only in cases where the application of the competition rules does not come to question. As the evaluation, regardless of different sub objectives of the areas, is finally aiming at the same goal, the welfare of the peoples of the EU, the outcome of the judgement of the case should nevertheless be similar regardless of the rules applied, eventually.

Euroopan unioni pyrkii tavoitteisiinsa luomalla esteettömät sisämarkkinat, joilla vallitsee tavaroiden, palvelujen, pääoman ja henkilöiden vapaa liikkuvuus. Yritysten välistä reilua ja avointa kilpailua pyritään edistämään. Jokaisen osapuolen – portinvartijan – joka kykenee estämään markkinoille pääsyn, on noudatettava tätä estäviä sääntöjä. Portinvartijoita ohjaavat keskeiset säännöt koostuvat Euroopan unionin toiminnasta tehdyn sopimuksen (SEUT) vapaata liikkuvuutta ja kilpailua koskevista artikloista. Näiden artiklojen määräyksiä tehostetaan lukuisilla alemman tason säännöksillä ja määräyksillä sekä periaatteilla, jotka Euroopan yhteisöjen tuomioistuin on kehittänyt oikeuskäytännössään. Tämän työn tarkoituksena on löytää keskeiset säännöt ja periaatteet, joilla ohjataan portinvartijoita, jotka voisivat estää pääsyn EU:n markkinoille, selvittää, ketkä ovat relevantteja portinvartijoita nykyisissä markkinaolosuhteissa, sekä tutkia näitä tahoja ohjaavien sääntöjen johdonmukaisuutta ja kattavuutta. Tässä hyödynnetään oikeusdogmaattista tutkimusmenetelmää. Sääntöjen muodostaman kokonaisuuden johdonmukaisuutta ja kattavuutta tarkastellaan käymällä ensin alueittain läpi keskeiset säännöt ja tärkeimmät näihin lisäohjausta antavat oikeustapaukset (säännöt ja periaatteet koostetaan taulukoksi). Tämän jälkeen rakennetaan vähitellen kokonaiskuva tarkastelun alla olleista yksityiskotaisista säännöistä. Vapaan liikkuvuuden sääntöjen ja kilpailusääntöjen soveltamisalaan kuuluvat toimijat yksilöidään. Tarkasteluun otetaan mukaan myös alustatalouteen liittyvien uusien liiketoimintamallien myötä syntyneet uudentyyppiset portinvartijat ja näitä ohjaavat säännöt (digimarkkinasäädös - Digital Markets Act, DMA). Sääntöjen systemaattinen vertailu ja tuomioistuimen sääntöjen soveltamisessa käyttämä logiikka paljastavat joitakin epämääräisyyksiä. Myös oikeusalueittain vaihteleva logiikka sääntöjen soveltamisessa ja mahdolliset päällekkäisyydet soveltamisaloissa herättävät kysymyksiä. Se, voiko vapaan liikkuvuuden sääntöjä soveltaa horisontaalisuhteissa, on olennaista etsittäessä toimivaa logiikkaa eri alojen sääntöjen soveltamiselle. Perinteisesti vapaan liikkuvuuden sääntöjen kohteena ovat olleet jäsenvaltiot ja kilpailusääntöjen kohteena yritykset, mutta viime vuosikymmeninä tuomioistuin on soveltanut vapaan liikkuvuuden lakeja myös ammattiliittoihin, urheilujärjestöihin ja jopa yksityisiin yrityksiin. Nyt kysymys kuuluukin: rajataanko vapaan liikkuvuuden sovellettavuutta horisontaalisuhteissa jotenkin, vai voidaanko molempia sääntötyyppejä soveltaa myös yksityisiin tahoihin? Jos voidaan, millaisella logiikalla päätetään mitä sääntöjä sovelletaan? Sääntöjen soveltamisen logiikka on erilainen eri alueilla: esimerkiksi kilpailulakien sovellettavuutta koskevia päätöksiä tehdessä arvioidaan mahdollisen portinvartijan markkinavoimaa, kun taas vapaan liikkuvuuden lakeja sovellettaessa portinvartijoiden ominaisuuksia, kuten kokoa, ei ole oikeustapauksissa näytetty huomioidun mitenkään. Työssä esitellään yksinkertaistettu kokonaistavoitteeseen nojaava malli sääntöjen soveltamisen selkeyttämiseksi. Vapaan liikkuvuuden sääntöjen horisontaalista soveltamista ehdotetaan sallittavaksi effect utile periaatteen mukaisesti, tarvittaessa. Kuitenkin digimarkkinasäädöksen tyyppisten lakien lisäksi myös kilpailusääntöjä on pidettävä erityislakeina, jolloin ne tulevan sovellettavaksi ennen vapaan liikkuvuuden sääntöjä. Näitä puolestaan on tarkoitus käyttää ensisijaisesti vain niissä tapauksissa, joissa kilpailusääntöjen soveltaminen ei tule kyseeseen. Koska arviointi, riippumatta alueiden erilaisista alatavoitteista, tähtää lopulta samaan päämäärään, hyvinvointiin, pitäisi tuloksen olla kokonaistavoitteen kannalta joka tapauksessa samanlainen riippumatta sovelletuista säännöistä.
Keywords: Free movement law, Competition law, Digital Markets Act, gatekeeper, EU internal market, horizontal application